PEMIKIRAN POLITIK MAHATMA GANDHI TENTANG AHIMSA DAN SATYAGRAHA TERHADAP KEKERASAN STRUKTURAL DI INDONESIA - Franky .; Lusia Astrika (Journal of Politic and Government Studies, 2019)
Structural violence is violence that occurs subtly and is not clearly visible but is resolved by the lives of many people. Such as corruption, religious intolerance, and drug trafficking in the area. Structural violence is often applied by the Indonesian government fully unconsciously through its policies. To overcome this, there is a figure who struggles to understand everything related to all kinds of violence. Gandhi is an anti-violent struggle figure from India who always holds the struggle with non-violent struggle. Gandhi's life was devoted to community service. Gandhi fought various kinds of resistance, including defense which clashed against religion. The purpose of this study was to analyze and rethink Mahatma Gandhi's political thinking against structural defenses consisting of religion in Indonesia.This study uses descriptive research methods and also literature studies. Type of research literature study is collecting materials in the form of Gandhi's handwriting works and organizing information relating to research. to draw conclusions. In receiving the data, the researcher collects Gandhi's works and also collects works written by others but is still relevant to the research objectives.The results of the research that has been done, that it improves the politics of Mahatma Gandhi about Ahimsa and Satyagraha has several agreed approvals in supporting the violence that unites religion in Indonesia. Because the politicians have raised policies related to problems in Indonesia. the struggle against which resulted in a victory for anti-violence fighters. Several perspectives and discussions submitted to the Indonesian government are to look back on their views on society, be more open to differences, and actively help the community in structural opposition. Instead it gives legitimacy to structural defense.Keywords: Satyagraha, Ahimsa, Gandhi, Structural Violence